REKONSTRUKSI PERDAMAIAN DALAM PENYIDIKAN TINDAK PIDANA LALU LINTAS BERDASARKAN HUKUM PROGRESIF - Dwi Wahyono (UNISSULA, 2014)
Implementation of criminal investigations sometimes lead to traffic irregularities. The settlement of peace in the criminal investigation of traffic based progressive law is expected to be used as a legal basis in the implementation of restorative justice in the investigation of criminal traffic offense. This research is descriptive analytic means of this study seeks to provide a full overview, in-depth about a situation. The method used in this research is empirical juridical approach. Results of this study were (1) the existence of the construction of peace as a legal umbrella in the implementation of restorative justice in the investigation of criminal offenses level of traffic carried by a model of peace between the victim and the perpetrator in trafficaccidents through mediation, investigators just hold on Article 235 paragraph (1) and (2) and Article 236 paragraph (2) of Law No. 22 of 2009 on Road Traffic and Road Transport and Police Discretion, expediency, humanity and justice contained in Article 18 paragraph (1) of Law No. 2 of 2002 on Indonesian National Police. (2) Reconstruction of peace in implementing restorativejustice in the investigation of criminal offenses level of traffic based progressive law based on peace between perpetrators and victims in the Crime of Traffic can serve as the basis for the termination of the investigation process of the Crime of Traffic.